Farewell to the Magic in the Translation of Witkacy - Танушевска, Лидија (Poznańskie Studia Slawistyczne, 2013)
This article reveals theoretic aspects on literary translation through the analyses of the translation of the novel Farewell to the autumn by Polish writer Stanislaw Ignacy Witkiewicz. It concerns the competences and skills a translator of literature should have. Among other topics which have been analyzed, there is the creativeness, knowledge of cultural differences, writing skills in the goal- language. The analyses prove that it’s not that simple to translate literature and that it’s a special type of translation in the typology of translations. The article presents a list of most commonly made mistakes by translators who are not yet fit to translate literature of this kind. Translation of highly rated literature is a kind of magic, because of the effect they produce on the reader, and the translator should be skilled in making the magic of the words.